Ефективність системи фінансового моніторингу в умовах безготівкового суспільства - Абрамов, Федір Володимирович (ДВНЗ "Придніпровська державна академія будівництва та архітектури", 2023)
В даній статті робиться спроба оцінити ефективність системи фінансового моніторингу в умовах безготівкового суспільства. Показано, що використання готівки для здійснення незаконних операцій є лише одним з інструментів, що дозволяють особам, що втягнуті в процес відмивання брудних грошей, вийти з під контролю системи фінансового моніторингу. Визначено, що основними чинниками, що спрощують розробку нових інструментів виходу з під контролю системи фінансового моніторингу, є: невідповідність призначення платежу реально проданому товару; використання загально прийнятого замінника офіційній грошовій одиниці; можливості використовувати незаконні доходи для купівлі товарів на тіньовому ринку. Доведено, що основною вадою системи фінансового моніторингу, є її негнучкість та нездатність ефективно протидіяти новим, раніше невідомим, схемам відмивання брудних грошей.

This article attempts to evaluate the effectiveness of the financial monitoring system in the conditions of a cashless society. It is shown that the use of cash to carry out illegal transactions is only one of many tools that allow persons involved in the process of laundering dirty money to escape the control of the financial monitoring system. As a result, focusing on fighting only with this tool will lead not so much to increasing the efficiency of the financial monitoring system, but to the reorientation of persons, engaged in laundering dirty money, to use other mechanisms of bypassing the financial monitoring system. It was determined that the main factors that simplify the development of new tools and mechanisms for getting out of the control of the financial monitoring system and reduce the effectiveness of the formal rules of financial monitoring are: inconsistency of the purpose of payment with the actual sold goods or services provided; the use of a generally accepted substitute for the official monetary unit; opportunities to use illegal/shadow income to buy goods on the shadow market. It is shown that in the case of application of the discrepancy between payment assignment and actual sold goods, the effectiveness of getting out of the control of the financial monitoring system will depend on the correctness of the choice of the accompanying goods. In the case of the use of a generally accepted substitute for the official monetary unit, the effectiveness of getting out of the control of the financial monitoring system will depend on the prevalence of this substitute. It has been proven that the main flaw of the financial monitoring system, which ultimately determines its low level of efficiency, is its inflexibility, not its inability to effectively counteract new, previously unknown, money laundering schemes. As a result, each fundamentally new money laundering scheme will remain operational and invisible to the financial monitoring system until the main mechanisms of its operation are revealed and changes are made to the formal rules of financial monitoring that will make its use impossible.
The effectiveness of the financial monitoring system in the conditions of a cashless society
Keywords: відмивання брудних грошей; формальні правила; ефективність; безготівкове суспільство; система фінансового моніторингу; money laundering; formal rules; efficiency; cashless society; financial monitoring system